2019
DOI: 10.2174/0929867325666181031132007
|View full text |Cite
|
Sign up to set email alerts
|

Aim for the Readers! Bromodomains As New Targets Against Chagas’ Disease

Abstract: Bromodomains recognize and bind acetyl-lysine residues present in histone and non-histone proteins in a specific manner. In the last decade they have raised as attractive targets for drug discovery because the miss-regulation of human bromodomains was discovered to be involved in the development of a large spectrum of diseases. However, targeting eukaryotic pathogens bromodomains continues to be almost unexplored. We and others have reported the essentiality of diverse bromodomain- containing proteins in proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 118 publications
0
9
0
Order By: Relevance
“…The bromo domain is evolutionarily conserved, consists of about 110 amino acids and shares a globular fold that comprises a left-handed bundle of four α-helices linked by two variable-loop regions, which is conserved across all bromo domains (Filippakopoulos et al 2012). A number of evidences have demonstrated that bromodomain-containing protein can be used as targets for the treatment of cancer and other diseases (Alonso et al 2019;Schulz et al 2015).…”
Section: Biological Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The bromo domain is evolutionarily conserved, consists of about 110 amino acids and shares a globular fold that comprises a left-handed bundle of four α-helices linked by two variable-loop regions, which is conserved across all bromo domains (Filippakopoulos et al 2012). A number of evidences have demonstrated that bromodomain-containing protein can be used as targets for the treatment of cancer and other diseases (Alonso et al 2019;Schulz et al 2015).…”
Section: Biological Contextmentioning
confidence: 99%
“…1. Except three non-proline residues (Ser2, Gly68 and Thr75), 1 H and 15 N backbone chemical shifts were assigned for almost all residues (97%). In addition, 95% of NH and 15 N, 97% of 13 C, and 90% of 1 The consensus chemical shift index (CSI), obtained from 1 Hα, 13 Cα and 13 Cβ chemical shifts (values of 1, 0, -1 indicate β-sheet, random coil and α-helical structure, respectively)…”
Section: Assignment and Data Depositionmentioning
confidence: 99%
“…The first indication that inhibiting acetylation modifiers could have antiprotozoal activity occurred in 1996 when Darkin-Rattray et al found that apicidin, a fungal metabolite, was cytotoxic to several protozoan species by disrupting histone acetylation [84]. Since then, inhibitors of KATs, KDACs, and more recently, BDPs have been investigated for their potential as antiprotozoan therapeutic targets [85,86].…”
Section: Exploring Protein Acetylation Regulatory Machinery As Drug Targets In Protozoan Parasitesmentioning
confidence: 99%
“…The BDs from TriTryp BDFs share limited identity among them as well as with any other eukaryotic or bacterial BDs 31 . The inner core is different in each domain and only a limited number of the hyper conserved amino acids are present, also the hydrophobic pocket is mostly constituted by non-identical amino acids with conserved hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%